Bildlichkeit und Begriff in den Zeichnungen zum 1. Werksatz Franz Erhard Walthers - Lorenzo Thelen (Tr@jectoires)
The present text is limited to the position of the diagrams and work drawings (Werkzeichnungen) inside the oeuvre of the German artist Franz Erhard Walther (*1939). These are read as side effects of the objects in the 1. Werksatz (1963-69). In them, the problem of communicability is addressed, while at the same time they stand on the threshold of abolishing the (art-)work. This “Janus-faced conception of the work” (Michael Lingner) sets out to make an aesthetic experience communicable. The focus is on the reciprocal intersection and overlapping of pictorial and conceptual elements within the work drawings. An approach that finds its material equivalent using paper on both sides.